Moringa oleifera enhances liver antioxidant status via elevation of antioxidant enzymes activity and counteracts paracetamol-induced hepatotoxicity. - Nanthini, Uma; Fakurazi, Sharida; Ithnin, Hairuszah (Nutrition Society of Malaysia, 2010)
This study investigated the role of antioxidant enzyme system following crude hydroethanolic extract of Moringa oleifera leaves (MO) in acute paracetamol (PCM) induced hepatotoxicity. Hydroethanolic extract (80%) of MO (200 mg/kg and 800 mg/kg; p.o) was pre-administered before a single oral dose of 3 g/kg PCM intoxication to male Sprague-Dawley rats. Pre-treatment of the extract was found to have reduced lipid peroxidation level when compared to the group treated with PCM only. The level of glutathione peroxidase (GPx), glutathione-S-transferase (GST) and glutathione reductase (GR) was restored to near normal in groups that were pre-treated with MO. Histopathological studies have further confirmed the hepatoprotective activity of MO compared to group treated with PCM only. The results obtained were comparable to silymarin (200 mg/kg; p.o). The MO extract was found to have significantly protected the liver against toxicity following PCM intoxication by enhancing the level of antioxidant enzyme activity.